Cervico mediastinal teratoma in adult: A very rare presentation - Sadrizadeh, Ali (Lung India, 2015)
Teratoma is a rare presentation in adult, specifically in cervico-mediastinal region. We reported two adult patients with diagnosis of cervico-mediastinal teratoma and operated them. In adult patients who present with cervico-mediastinal mass, benign teratoma could be one of a differential diagnosis although it is a rare presentation.